1996
DOI: 10.1111/j.1540-8159.1996.tb03390.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Asynchronous Left Ventricular Relaxation by Doppler Echocardiography During Ventricular Pacing with AV Synchrony (VDD): Comparison with Atrial Pacing (AAI)

Abstract: The effect of right ventricular pacing on left ventricular relaxation was studied in 13 patients (age 62 +/- 3 years), with the atrial sensing ventricular pacing mode (VDD). A control group of similar age (64 +/- 4 years) consisted of 11 patients with atrial pacing (AAI). The timing of events was determined in both groups at similar R-R intervals (921 +/- 77 ms vs 967 +/- 37 ms). The loading conditions as estimated by peak systolic wall stress (afterload) and end-diastolic left ventricular dimensions (preload)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Further, there was a selection of a subgroup of patients with VVIR pacemakers who had tolerated long-term ventricular stimulation without developing chronic atrial fibrillation. It is possible that the patients in the present study, who had been paced in VVI pacing for an extended period of time, may be more dependent upon atrioventricular synchrony than others due to remodelling of the ventricles [24,25] .…”
Section: Improved Quality Of Life Following Dual Chamber Pacing 495mentioning
confidence: 98%
“…Further, there was a selection of a subgroup of patients with VVIR pacemakers who had tolerated long-term ventricular stimulation without developing chronic atrial fibrillation. It is possible that the patients in the present study, who had been paced in VVI pacing for an extended period of time, may be more dependent upon atrioventricular synchrony than others due to remodelling of the ventricles [24,25] .…”
Section: Improved Quality Of Life Following Dual Chamber Pacing 495mentioning
confidence: 98%
“…Looking at conventional Doppler parameters, some data suggest that VP, compared to atrial pacing alone, prolongs IVRT [22, 23]. Our finding of longer IVRT and deceleration time in patients with VP together with decreased E/A ratio and TDI-Ea measures suggest that VP results in more impaired relaxation.…”
Section: Discussionmentioning
confidence: 50%
“…Despite the presence of atrial systole, RV stimulation in dual-chamber devices may still adversely affect the overall LV systolic performance due to the profoundly modified interventricular septal motion [22, 23]. In this regard, there are discrepant results on whether VP reduces [24] or does not affect LV EF [25].…”
Section: Discussionmentioning
confidence: 94%
“…First, the nonphysiological electrical excitation of the myocardium resulted in asynchronous contraction of the left ventricle. The peak velocity of the mitral annulus systolic wave (Sm), proven to reflect the peak rate of the left ventricular pressure rise during contraction (peak dP / dt) [15], decreased after right ventricular apical pacing [8]. Secondly, several parameters concerning diastolic function were impaired by DDD pacing.…”
Section: Discussionmentioning
confidence: 99%
“…The intraventricular flow driven by the pressure gradient generated from the physiologic nonuniformity can be used to investigate the disruption of ''optimal tuning'' of cardiac muscle-pump performance in various pathologic conditions [5,6]. Using the continuous wave Doppler echocardiography, previous studies have shown the intraventricular flow during isovolumic relaxation produced by right ventricular pacing [7,8]. The color M-mode echocardiography, having the advantage of temporal and spatial resolution, can describe the influence on isovolumic relaxation flow by disrupted nonuniformity more instructively than the conventional Doppler method [6,9].…”
mentioning
confidence: 99%